Pengaruh Pola Asuh Orang Tua Terhadap Kemandirian Belajar Peserta Didik Kelas Xi Di SMA Negeri 4 Sijunjung - Mandela, Sri Gusti; Kardo, Rici; Usman, Citra Imelda (Universitas Pakuan, 2025)
The Influence Of Parental Parenting Styles On The Learning Independence Of Grade Xi Students At State High School 4 SijunjungThis research is motivated by the existence of students who experience a lack of learning independence and students do not know about learning independence. This study aims to determine: 1) Parenting patterns of parents in class XI students at SMA Negeri 4 Sijunjung. 2) Learning independence of class XI students at SMA Negeri 4 Sijunjung. 3) Describe the influence of parenting patterns on learning independence of class XI students at SMA Negeri 4 Sijunjung. This study uses a descriptive quantitative research method. with a population of 94 people, the sampling technique is total sampling. The instrument used in this study is a questionnaire. Data analysis in this study is a percentage and simple linear regression. The results of this study show: 1) Parenting patterns of class XI students at SMA Negeri 4 Sijunjung are in the high category. 2) Learning independence of class XI students at SMA Negeri 4 Sijunjung is in the high category. 3) The results of the analysis indicate that there is a significant influence (Ha) between the influence of parenting patterns on student learning independence. A significance value of 0.200 ≥ 0.05 indicates a very strong category. Therefore, it can be concluded that parenting patterns have a significant influence on students' learning independence. This study recommends that guidance and counseling teachers design service programs that focus on good learning independence for students.